Management of solid waste produced in a university restaurant on an expansion campus (Research, Society and Development, 2020)
In the context of food waste and solid waste production, the Food and Nutrition Units (UAN) deserve special focus, in view of the permanent use of resources and the increase in the generation of waste, as the daily assessment of leftovers is one of the measures most used as control of a UAN. In view of the above, this study aimed to characterize and analyze solid organic and inorganic residues produced in a university restaurant in a public university. For this, all residues in different stages of the lunch production process were weighed for two consecutive weeks and the correction factor, total leftovers and percentages of rest ingestion were calculated. The results found revealed that the average per capita of solid waste generated in the unit was 0.440 Kg/diner/day, where the processing area had the largest residue generating area, being the largest portion caused by the pre-preparation of vegetables and fruits , followed by meat pre-preparation, where of the 19 items analyzed, 10 were above the average values observed in the literature, 05 were within the average obtained by the authors and 04 below the average found. The Unit serves an average of 174 lunches / day obtaining an average of 23.75 kg/leftover/day or 19% of its production, being able to feed the number of 79 people/days with leftovers. Thus, it is inferred that the characterization and determination of correction factors, percentage of leftovers and leftovers proved to be important indicators for measuring food waste in the Unit in order to subsidize future systemic actions for rationalization and management of produced solid waste.